Security of the Organization in The Context of The Data Protection Officer - Malgorzata KOCHANOWICZ (Communications of International Proceedings, 2021)
The purpose of this article is to present the role and position of the Data Protection Officer (hereinafter referred to as the: DPO) that should play in ensuring the security of the organization. The article is based on the surveys of the awareness of employees processing personal data as to the DPO existence in their organization.
Keywords: Security; Data Protection Officer; Organisation.